Beyond Boundaries: Using Liquid Languages - Interview with Britta Schneider about “Liquid Languages” (Gragoatá, 2021)
Data from plurilingual Belize shows that not everyone recognizes stability as an essential feature of aspoken language. Belizeans consider the use of Kriol as a symbol of belonging but foreground its readiness for variation across communities in space and time. Their use of liquid languages is a different form of cultural construction than the one our textbooks show. It questions a good part of linguistics and reveals its possibly Eurocentric point of view.